The Regression Analysis through Matlab of the Electrical Parameters in a Hydropower Plant - Virtyt Lesha (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
This paper presents the nonlinear regression analysis between the transformer's measurable parameters (temperature of oil and winding) and the electrical parameters (hydropower plant's aggregate). There is not a specific mathematical function that connects the winding and oil temperature with the generator voltage, generator current, active power, reactive power, etc. Therefore to find the connection between them, statistical methods are needed. So, the work in this article consists in putting as a position variable of the electrical parameters of an aggregate in a hydropower plant against the parameters such as transformer's winding and oil temperature. Through Matlab, these data are analyzed through the sixth order nonlinear polynomial regression giving the determination coefficients. he reason for the use of the nonlinear regression of this order is related to the fact that the use of nonlinear regression of higher orders does not represent more accurate apparent than nonlinear regression of higher orders. On the other side the regressions with lower orders has not been used because their accuracy is significantly lower than the order of regression in question.
Keywords: C20; L9; 330; technology; Matlab; nonlinear regression; winding temperature; oil temperature